Tujuan Pendidikan Islam: Dunia, Akhirat dan Pembentukan Karakter Muslim dalam Membentuk Individu yang Berakhlak dan Berkontribusi Positif - Mukhlis Mukhlis; Ahyar Rasyidi; Husna Husna (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This research aims to delve deeper into the objectives of Islamic education, encompassing goals in both the worldly life, the Hereafter, and the formation of Muslim character. The study goes beyond exploring academic knowledge, delving into the role of Islamic education as a transformative force in shaping moral and ethical values, as well as moral courage amidst the challenges of the modern era. The methodology employed in this research is literature review (library research). The study utilizes a library research approach by searching various articles, journals, and other scholarly works related to pre-defined keywords. Subsequently, the researcher collects, analyzes, and selects relevant sources to draw conclusions. The significance of this research lies in its ability to summarize how Islamic education not only prepares individuals for contemporary life but also equips them with values that guide their journey in the Hereafter. In tandem with this, the research highlights how Islamic education responds to contemporary issues, providing a relevant framework for the global challenges faced by Muslim communities today. The findings of this research offer a nuanced and layered perspective on the meaning and urgency of Islamic education in shaping individuals with high moral character who can contribute positively to society at large Keywords: Islamic Education, Worldly Life, Hereafter, Character.